ISTIHSAN DAN PEMBAHARUAN HUKUM ISLAM - Fitriyani Fitriyani (TAHKIM, 2018)
Istihsan a legal move from a problem on a similar one for their arguments stronger. While legal reform is a historical necessity for social phenomena are not static or fixed, but constantly changing. So, in addition to permanent, laws have changed. Law other than static and fixed, at the same time also changed and updated to conform with the development and needs of the community. Islamic law viewed as a product of science as well as science, as well as from the perspective of tajdid- necessarily require revision and law reform. istihsan basically also one of the methods in berijtihad because istihsan is one way to find solutions to the problems are not resolved by the general rules in fiqh by turning to the rules of partial.